FACTORS AFFECTING ADHERENCE TO MEDICATIONS IN HYPERTENSIVE PATIENTS VISITING A TEACHING HOSPITAL IN KHYBER PAKHTUNKHWA - Yasmin Akhtar; Afridi, Muhammad Abdur Rahman; Zafar Ali; Atta Muhammad Khan (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine various factors affecting adherence to antihypertensive medications. Methodology: An observational descriptive study conducted in Medical Out-Patient Department of Lady Reading Hospital Peshawar from June 2019 to October 2019. A total of 250 adult hypertensive patients of both genders were included. Adherence to medication was assessed using ‘proportion of days covered’ method. A score of >80% was considered as ‘good adherence’. Four factors affecting adherence, were specifically studied: ‘Asymptomatic state’ of the patient; ‘Affordability of medications; influence of the ‘Local GP’; and ‘Adverse effects’ of the drugs. SPSS version 21 used for data analysis; correlation carried out; chi square (x2) p<0.05 considered statistically significant. Results: Out of 250 patients, 67(26.8%) were males and 183(73.2%) females. Mean age was 56.13 years ±10.30 SD. Overall, 108(43.2%) patients had good adherence and 142(56.8%) had poor adherence (x2(4)=250.0, r(4)=0.89, p<0.001). The most common factor affecting adherence was the ‘asymptomatic’ state (56.3%, p=0.001); followed by ‘non-affordability’ (21.1%, p=0.001); ‘Local GP’ influence (14.8%, p=0.001); and drugs’ adverse effects (7.8%, p=0.003). Patients taking ‘combination’ of drugs, ARBs and BBs had 60%, 58% and 18% adherence, respectively (x2(4)=35.41, r(4)=0.50, p=0.018). Conclusion: Factors associated with poor adherence to medications include ‘asymptomatic state’ of the patient, ‘non-affordability’ of drugs, ‘influence of local practitioner’ and ‘adverse effects’ of drugs; all significantly inversely correlated with adherence. Economic status, duration of hypertension and drug groups also significantly correlated with adherence.